2021
DOI: 10.2147/opth.s287573
|View full text |Cite
|
Sign up to set email alerts
|

Time Utilization and Refractive Prediction Enhancement Associated with Intraoperative Aberrometry Use During Cataract Surgery

Abstract: Purpose: To evaluate the time cost of intraoperative aberrometry (IA), to compare IA prediction error to the prediction error associated with conventional formulas using preoperative calculations (PC) and evaluate when IA provides clinically relevant benefit. Methods: This is a retrospective study of eyes that underwent cataract phacoemulsification surgery with IA at an academic eye center. IA versus PC prediction error were compared amongst various preoperative and intraoperative characteristics. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…In post-corneal refractive surgery eyes, measurement inaccuracies pose additional challenges for ophthalmologists attempting to calculate IOL power. 24,25 Intraoperative aberrometry may help to reduce errors in IOL power calculation, especially in those with extremes in axial length or prior refractive surgery 26,28 by measuring the eye's refractive power in the aphakic state, thus accounting for both the anterior and posterior curvature and refractive index of the cornea. 22 The precision and quality of the intraoperative wavefront aberrometry measurements, however, may be affected by its lower repeatability, 24 the need to optimize IOP, hydration and wound integrity, the presence of bubbles in the visual axis, globe distortion due to eyelid speculum pressure, and patient cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…In post-corneal refractive surgery eyes, measurement inaccuracies pose additional challenges for ophthalmologists attempting to calculate IOL power. 24,25 Intraoperative aberrometry may help to reduce errors in IOL power calculation, especially in those with extremes in axial length or prior refractive surgery 26,28 by measuring the eye's refractive power in the aphakic state, thus accounting for both the anterior and posterior curvature and refractive index of the cornea. 22 The precision and quality of the intraoperative wavefront aberrometry measurements, however, may be affected by its lower repeatability, 24 the need to optimize IOP, hydration and wound integrity, the presence of bubbles in the visual axis, globe distortion due to eyelid speculum pressure, and patient cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IA is expected to improve the refractive outcome of patients with axial myopia. 3 , 10 Previous reports on IA accuracy mainly focused on achieving emmetropia, although intentional myopia is another common choice for patients with axial myopia. In this study, we aimed to investigate the influence of intentional myopia on the refractive prediction of IA.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the percentage of patients within ±0.5D of target was 56% for intraoperative aberrometry and 47% for Barrett-True K ( P = 0.289) [28 ▪ ]. Other studies with smaller numbers of post-hyperopic ablation patients have shown a similar mean absolute error of approximately 0.5D without significant difference from preoperative calculations [20 ▪▪ ,29,45]. Intraoperative aberrometry may be more accurate in post-hyperopic ablation cases with short axial length in comparison to those with intermediate or long axial length [28 ▪ ].…”
Section: Intraoperative Aberrometry In Eyes With History Of Refractiv...mentioning
confidence: 91%
“…In the multivariate regression model by Christopher et al [20 ▪▪ ] for eyes with greatest potential benefit of intraoperative aberrometry, post-radial keratotomy eyes had an odds ratio of 5.5 for intraoperative aberrometry to have prediction error less than 0.5D when preoperative calculations would have a prediction error greater than 0.5D. This was the highest odds ratio of the examined variables, and would suggest that intraoperative aberrometry might be particularly advantageous in post-radial keratotomy eyes [20 ▪▪ ]. However, other recent studies have instead found that intraoperative aberrometry has similar refractive outcomes to preoperative calculations [28 ▪ ,29,43,44].…”
Section: Intraoperative Aberrometry In Eyes With History Of Refractiv...mentioning
confidence: 99%
See 1 more Smart Citation